BERFIKIR TEORITIS DAN GRAND TEORI DALAM ILMU SOSIAL - ULFA, SANTI NOFRIA; FITRISIA, AZMI; FATIMAH , SITI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
This article discusses critical thinking and grand theory in social sciences and their relationship in the social context of how to think theoretically in its application and development of grand theory in social sciences, writing this article uses a library method or literature study. Theoretical thinking uses a way to analyze, evaluate, and interpret information objectively to explain social phenomena that have the purpose of using abstract concepts and ideologies. Grand theory in social sciences seeks to provide a comprehensive framework of understanding of social structure, power dynamics, and the relationship between individuals and society. This article discusses how critical thinking and grand theory help in research studies or social scientists to analyze the truth and develop more relevant approaches through a review of the main theories in social sciences in the ever-evolving changes. It is concluded that critical thinking is an important element in formulating and developing grand theory in social sciences that can provide in-depth insights into social structure and social change. ABSTRAKArtikel ini membahas terkait berfikir kritis dan grand teori dalam ilmu sosial serta ketarkaitan keduanya dalam konteks sosial bagaimana berfikir teoritis dalam penerapannya dan pengembangan grand teori dalam ilmu sosial, penulisan artikel ini menggunakan motede kepustakaan atau studi literatur. Berfikir teoritis menggunaan cara untuk menganalisis, mengevaluasi, dan menafsirkan informasi secara objektif untuk menjelaskan fenomena sosial yang memiliki tujuan penggunaan konsep-konsep dan ideologi abstrak. Grand teori dalam ilmu sosial berusaha untuk memberikan kerangka pemahaman yang menyeluruh mengenai struktur sosial, dinamika kekuasaan, serta hubungan antara individu dan masyarakat. Artikel ini membahas bagaimana berpikir kritis dan grand teori membantu dalam kajian penelitian atai ilmuan sosial untuk menganalisa kebenaran dan mengembangkan pendekatan yang lebih relevan melalui tinjauan terhadap teori-teori utama dalam ilmu sosial dalam perubahan yang terus berkembang. Maka disimpulkan bahwa berpikir kritis merupakan elemen penting dalam merumuskan dan mengembangkan grand teori dalam ilmu sosial yang dapat memberikan wawasan mendalam tentang struktur sosial dan perubahan sosial.